Critical Role of CD6highCD4+ T Cells in Driving Th1/Th17 Cell Immune Responses and Mucosal Inflammation in IBD. (3rd November 2018) - Ma, Caiyun; Wu, Wei; Lin, Ritian; Ge, Yadong; Zhang, Cui; Sun, Suofeng; Cong, Yingzi; Li, Xiuling; Liu, Zhanju
Abstract: Background and Aims: CD6 is a crucial regulator of T cell activation and is implicated in the pathogenesis of multiple autoimmune diseases. ALCAM is the first identified endogenous ligand of CD6. We sought to investigate potential roles of CD6 in regulating intestinal mucosal inflammation in inflammatory bowel disease [IBD]. Methods: We analysed the expression of CD6 and ALCAM in the inflamed mucosa of IBD patients using qRT-PCR and immunohistochemistry. Phenotypic properties of CD6 low/− and CD6 high CD4 + T cells were determined by flow cytometry, qRT-PCR, and ELISA. ALCAM Fc chimeric protein was used to evaluate the role of CD6–ALCAM engagement in regulating IBD CD4 + T cell activation and differentiation. Results: Expression of CD6 and its ligand ALCAM was markedly increased in the inflamed mucosa of IBD patients compared with that in normal controls, and was significantly correlated with disease activity indices of IBD patients. Interestingly, CD6 high CD4 + T cells of IBD patients exhibited significantly higher pathogenicity compared with CD6 low/− CD4 + T cells, characterized by enhanced T cell activation and preferential Th1 and Th17 cell phenotypes, but a markedly decreased proportion of nTreg [CD25 high Foxp3 +, CD25 high CD127 low ] cells. Importantly, inclusion of ALCAM Fc chimeric protein significantly facilitated IBD CD4 + T cell, especially CD6 high CD4+ T cell, differentiation into Th1/Th17 cells compared with hIgG1 Fc–treated controls. Conclusions: These data indicate that overexpression of CD6 and ALCAM in the inflamed mucosa of IBD patients accelerates intestinal mucosal immune responses via promoting CD4 + T cell proliferation and differentiation into Th1/Th17 cells. Thus, CD6 may serve as a novel therapeutic target for treatment of IBD.